Hydrothermal carbonization (HTC) of wheat straw: Influence of feedwater pH prepared by acetic acid and potassium hydroxide. (April 2015) - Reza, M. Toufiq; Rottler, Erwin; Herklotz, Laureen; Wirth, Benjamin
Highlights: HTC of straw was performed varying feedwater pH from 2 to 12 for 200 and 260 °C. Lower pH at each temperature shows maximum elemental carbon and minimum oxygen. HTC process liquid pH were 2.9–4.1 regardless to feedwater pH and HTC temperature. HMF and furfural were increasing for HTC 200 process liquid with acidic feed pH. Abstract: In this study, influence of feedwater pH (2–12) was studied for hydrothermal carbonization (HTC) of wheat straw at 200 and 260 °C. Acetic acid and KOH were used as acidic and basic medium, respectively. Hydrochars were characterized by elemental and fiber analyses, SEM, surface area, pore volume and size, and ATR-FTIR, while HTC process liquids were analyzed by HPLC and GC. Both hydrochar and HTC process liquid qualities vary with feedwater pH. At acidic pH, cellulose and elemental carbon increase in hydrochar, while hemicellulose and pseudo-lignin decrease. Hydrochars produced at pH 2 feedwater has 2.7 times larger surface area than that produced at pH 12. It also has the largest pore volume (1.1 × 10 −1 ml g −1 ) and pore size (20.2 nm). Organic acids were increasing, while sugars were decreasing in case of basic feedwater, however, phenolic compounds were present only at 260 °C and their concentrations were increasing in basic feedwater.